To find the equation of the line in the form \( y = mx + b \), we need to determine the slope \( m \) and the y-intercept \( b \) based on the points given: \( (0, -3) \) and \( (1, 0) \).
Step 1: Calculate the slope (m)
The formula for the slope \( m \) between two points \( (x_1, y_1) \) and \( (x_2, y_2) \) is:
\[ m = \frac{y_2 - y_1}{x_2 - x_1} \]
Using the points \( (0, -3) \) as \( (x_1, y_1) \) and \( (1, 0) \) as \( (x_2, y_2) \):
\[ m = \frac{0 - (-3)}{1 - 0} = \frac{0 + 3}{1} = \frac{3}{1} = 3 \]
Step 2: Determine the y-intercept (b)
To find the y-intercept \( b \), we can use the point \( (0, -3) \), which directly gives us:
\[ b = -3 \]
Step 3: Write the equation
Now we can write the equation of the line in slope-intercept form \( y = mx + b \):
\[ y = 3x - 3 \]
Thus, the correct response is:
\( y = 3x - 3 \)